Antecedents of Traveller Identification and Satisfaction As a Consequence of Traveller Decisions - Muhammad Aqsa; Aetken Ibrahim; Suparman Parintak; Anne Attas (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background:This research is motivated by the North Luwu Regional Government's concerns that in order to increase and attract visitor interest in the Rinding Allo Tourism Village, Rongkong District, North Luwu Regency, tourist attraction managers must develop the potential of tourist attractions and maximize promotional activities for tourism potential to consumers, so as to foster desire. make visits with the hope of creating tourist satisfaction.Purpose:This research aims to see the extent of the influence of tourist attractions and promotions on tourist satisfaction through tourists' visiting decisions.Methodology:This research is quantitative research with an associative approach with data collection instruments using questionnaires. The sample consisted of 100 respondents, with using the margin of error (MOE) formula. The data that has been collected will be subjected to verification and descriptive analysis with statistical tool SmartPLS.Finding:The research results show that the attractiveness of tourist attractions and promotions has a positive and significant effect on the decision to visit. The decision to visit has a positive and significant effect on tourist satisfaction. The attractiveness of tourist attractions and promotions has a positive and significant effect on tourist satisfaction. The attractiveness of tourist attractions and promotions has a positive and significant effect on tourist satisfaction through the decision to visit.Conclusion: Increasing infrastructure and supporting facilities can increase tourism potential and wider use of promotional media such as social media promotions can increase the reach of promotions carried out.Originality/Value (State of The Art): Research on the Rinding Allo Tourism Village is the first research conducted using tourist attraction and promotion variables to highlight local wisdom and regional culture in attracting tourists and increasing tourist satisfaction. Keywords: attraction, tourist attractions, promotion, tourist visiting decisions, tourist satisfaction